Algae explosive growth mechanism enabling weather-like forecast of harmful algal blooms - Tian, Rongxiang (Sci Rep, 2018)
As a global problem in coastal environments, harmful algal blooms (HABs) have seriously affected the health of coastal ecosystems and regional economies. Here we report an aerosol-trigger mechanism for the occurrence of HABs based on long-term field data and laboratory experiments. The occurrence times of HABs and aerosol events had a significant correlation from 2005 to 2013 in the East China Sea, indicating that aerosol transport was probably an alternative trigger of HABs. HABs mostly occur in the transition time between winter and summer, during which northwest monsoon transport substantial aerosol (rich in phosphate, iron and other trace metals) to coastal waters, as revealed by chemical measurements, transmission electron microscope and electron microprober results. Such nutrients can stimulate algal growth in our incubation experiments, suggesting that such aerosol transport can be important nutrient sources for the East China Sea where phytoplankton growth is relatively phosphate limited. Air-borne nutrients are available for algal growth by rapid downward air flow, which additional results a clear weather condition, and thus adequate light intensity for algal growth. At last, the transition from northwest monsoon to warm southwest monsoon establishes favorable seawater temperature for algal blooms. Such weather-related aerosol-trigger mechanism suggests possibly forecast of HABs.